Development of a structural gross pollutant trap model / Renga Rao Krishnamoorthy, Prof. Ir. Dr. Ruslan Hassan and Jurina Jaafar - Krishnamoorthy, Renga Rao; Hassan, Ruslan; Jaafar, Jurina (2006)
Stormwater runoff is responsible for transporting many of the pollutants, which are degrading our waterways and rivers. The common pollutants from urban sources are sediments, nutrients, heavy metals, litter and debris, oil and surfactants and many more. The control of storm water pollution is an integral part of the Urban Storm water Management for Malaysia (MSMA). A structural gross pollutant trap model was developed in the aims of controlling the pollutant at source before it gets to nearby ponds, rivers and or waterways.